The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/md9.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions to improve the success of electrical cardioversion in patients with atrial fibrillation

Abstract: Background: Electrical cardioversion (ECV) is a common management strategy for atrial fibrillation (AF). ECV contains multiple modifiable components, including pad size and placement, shock energy, and waveform phases. Guidance on optimal technique, however, is limited. A comprehensive review of interventions used to increase ECV success will guide ideal clinical practice and identify techniques that could be studied in future randomized controlled trials. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Our systematic review and meta-analysis of randomized trials also concluded that existing data are insufficient to ascertain optimal pad placement when using the modern standard of biphasic, maximal energy waveforms. 2 Only 1 trial compared anterior-posterior and anterior-lateral placement while using fixed-maximal energy with a biphasic waveform; it was a substudy of only 160 patients and was neither adequately powered nor specifically designed to address this question. 5 Although the trial by Schmidt et al 1 is rigorous and internally valid, it used an escalating energy protocol, which limits its external validity.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Our systematic review and meta-analysis of randomized trials also concluded that existing data are insufficient to ascertain optimal pad placement when using the modern standard of biphasic, maximal energy waveforms. 2 Only 1 trial compared anterior-posterior and anterior-lateral placement while using fixed-maximal energy with a biphasic waveform; it was a substudy of only 160 patients and was neither adequately powered nor specifically designed to address this question. 5 Although the trial by Schmidt et al 1 is rigorous and internally valid, it used an escalating energy protocol, which limits its external validity.…”
Section: To the Editormentioning
confidence: 99%
“…Our systematic review and meta-analysis of randomized trials regarding nonpharmacologic interventions to improve cardioversion success, 2 presented at the American Heart Association Scientific Sessions in 2021, found that fixed-maximal energy protocols were superior to escalating protocols for first shock success in converting atrial fibrillation to sinus rhythm (relative risk, 1.62 [95% CI, 1.33–1.98]). Minimizing the number of shocks required to convert atrial fibrillation to sinus rhythm is desirable, because it leads to shorter procedure duration and reduced requirements for sedation.…”
Section: To the Editormentioning
confidence: 99%
“…We pre-registered the protocol with Open Science Framework (DOI:10.17605/OSF.IO/FTU57). 16 We list the differences between the registered and final protocol in see Supplementary material online , Appendix S1 .…”
Section: Methodsmentioning
confidence: 99%
“…We searched CENTRAL, MEDLINE, and EMBASE from inception to October 2022 and searched the grey literature. 16 An academic librarian reviewed the search strategies (see Supplementary material online , Appendix S2 ).…”
Section: Methodsmentioning
confidence: 99%